1995
DOI: 10.1159/000119168
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Skin Potential Response and Psychopathology in Patients with Affective Disorders

Abstract: The correlation between the degree of psychopathology (assessed by the Minnesota Multiphasic Personality Inventory, MMPI) and sympathetic function (assessed by the skin potential response to somatosensory stimuli) was evaluated in 209 patients with affective disorders. A number of skin potential parameters (skin potential levels, negative fluctuations of first derivative of skin potential, negative areas in phase plane analysis, differences between last and initial average potentials and between the last avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Skin potential responses to unexpected sound in clomi pramine-injected rats resembled electrical responses found in human depression [18][19][20][21]39]. When a stronger stimulus was employed (a mild nociceptive stimulus giv en by ammonia vapor exposure) no differences were found in skin potential response between clomipramineand saline-injected rats, nor in the rate of habituation to repetitive ammonia vapor stimulus.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Skin potential responses to unexpected sound in clomi pramine-injected rats resembled electrical responses found in human depression [18][19][20][21]39]. When a stronger stimulus was employed (a mild nociceptive stimulus giv en by ammonia vapor exposure) no differences were found in skin potential response between clomipramineand saline-injected rats, nor in the rate of habituation to repetitive ammonia vapor stimulus.…”
Section: Discussionmentioning
confidence: 71%
“…For example, in a recent study we reported a decreased parasympathetic activity (as evaluated by car diovascular tests of autonomic function) and an increased sympathetic activity (as indicated by larger skin potential responses) in patients with major depression [20], In another study, we reported that sympathetic activation, as assessed by skin potential responses, correlated with the severity of the disease in a sample of patients with affec tive disorders [21], Despite the growing importance of electrodermal ac tivity as a marker of sympathetic activity, an experimen tal model for assessing electrodermal responses in freely moving, unrestrained animals is yet lacking. Published animal studies employed recordings taken from the foot pads of cats and rats, regions known to be rich in sweat glands [5,22], Obviously, this experimental design inter feres with free ambulation of the animals.…”
Section: Introductionmentioning
confidence: 86%
“…In migraineurs, verapamil reduced an exaggerated sympathetic response, but in the investigation of HRV in CH patients during tilt, we found no difference in analyzed parameters in the response to tilt between patients being treated with verapamil and those not . Another factor that should be kept in mind is psychiatric comorbidity as it might affect autonomic function, which has been demonstrated in other primary headaches . Further, studying autonomic tone during spontaneous attacks during the day may be challenging as autonomic tone fluctuates with changing levels of activity, mood, etc.…”
Section: Discussionmentioning
confidence: 75%
“…It can be argued that MMPI is a rather insensitive method, and that any psychopathological assessment performed by combining the clinically relevant MMPI scales may be relatively crude. However, PI was employed for examining the accompanying psychopathology in Wilson's disease (Medalia and Scheinberg, 1989), and in a study examining the correlation between the degree of psychopathology and sympathetic function (as evaluated by the electrodermic response to somatosensory stimuli) in 209 patients with affective disorders, PI correlated positively with sympathetic activity (Guinjoan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we reported that electrodermal responses to sensory stimuli (an index of sympathetic activation) correlated positively with PI in a sample of 209 patients with affective disorders (Guinjoan et al, 1995).…”
Section: Introductionmentioning
confidence: 90%